(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2021)
This study aimed to demonstrate the effect of regulatory characteristics on the quality of accounting earnings and the detection of earnings management practices in banks listed on the Damascus Stock Exchange based on the Jones model modified by Dechow et al. (1995) and in the disclosure of these practices. To achieve these goals, the secondary data published in the financial reports of the 14 banks listed on the Damascus Stock Exchange, were used, and the sample included 11 traditional banks, after excluding Islamic banks. The study was conducted during the period 2015-2018. The results of the study showed that 80% of the observations of the banks listed on the Damascus Stock Exchange have practiced earnings management during the study period, and the study also found that volume and financial leverage have an adverse effect on the quality of earnings, while the effect of earnings ability was expelled but not significantly, and showed no A statistically significant effect of regulatory characteristics on the quality of earnings.